Effect of Profile Morphology on Root Development of Sal (Shorea robusta) Seedlings - Seth, S. K.; Srivastava, P. B. L. (Indian Forester, 1972)
The article describes the effect of stratified profiles consisting of alternate layers of soil and sand of different thickness on root development of sal seedlings. The seedlings were grown in two separate profiles of 18 inches thickness, one consisting of 6 inch thick sand layer in between two 6 inch thick soil layers and the other of 6 alternate layers of soil and sand each 3 inch thick with a soil layer at the top. The results indicate that 6 inch thick sand layer underlying soil layer of equal depth is unfavourable for root development. It appears that a 3 inch thick top soil layer is incapable of supplying adequate amount of moisture and nutrients to meet the demand of seedlings and that 3 inch thick sand layer is not an impediment for deep root penetration. The inference may be drawn that the soli profiles having sand layers 6 inch or more in thickness, especially if they underlie a thin top soil layer, may prove detrimental to the growth of sal seedlings particularly during the establishment stage and may be the cause of die-back or stagnation in such localities. On the contrary lengthy roots stimulated by 3 inch thick alternate layers of soil and sand may be better able to tolerate drought conditions than those produced in the profile having a 6 inch thick intermediate sand layer where the root development was arrested at the transition boundary between soil and sand.